Exploring the influence of bank traits and economic factors on the profitability of Indonesian Islamic commercial banks - Al-Shaghdari, Fahd Mohammed Obad; Ibrahim, Kamal Mustafa Saeid (IIUM Press, 2024)
The present research aims to investigate the impact of banks' characteristics and macroeconomic factors on the profitability of Islamic commercial banks in Indonesia. This study utilizes a quantitative research technique that involves the application of numerical measurements and analysis to investigate the factors that influence the profitability of Islamic commercial banks. This study investigates the influence of internal factors, including equity financing, bank size, and debt financing, as well as external factors, such as the GDP growth rate and interest rate, on the profitability of Islamic banks in Indonesia. This study utilizes panel data, also known as longitudinal data. The dataset comprises a panel of 11 Islamic commercial banks located in Indonesia. The data were obtained from the DataStream Database and the balance sheet for the period between 2012 and 2022, yielding a total of 121 observations. The results suggest that equity financing, bank size, interest rate, and GDP growth rate significantly influence the profitability of Islamic commercial banks in Indonesia. These characteristics are critical in ensuring the success, profitability, and overall performance enhancement of Islamic commercial banks. However, the internal factor of debt financing does not exert a substantial influence on the profitability of Islamic commercial banks in Indonesia. The study suggests that Islamic banks, especially in Indonesia, should strengthen profit-and-loss sharing instruments in order to reduce inequalities and promote economic growth.